Opioid Free Anaesthesia and Cancer - Malo-Manso, Alfredo; Raigon-Ponferrada, Aida; Diaz-Crespo, Julia; Escalona-Belmonte, Juan J.; Cruz-Mañas, Jose; Guerrero-Orriach, Jose L. (Current Pharmaceutical Design, 2019)
Opioid-free anesthesia is revolutionizing anesthetic practices for its potential benefits in selected patients. Opioid-free anesthesia represents a step forward in anesthetic practice as it has been suggested to provide potential clinical benefits for selected patients. Opioid-free anesthesia spares the use of opioids and involves the administration of multiple adjuvant anesthetics, which may have an impact on cancer progression. All this have added to the growing interest in the immune response to anesthetics, making opioid-free anesthesia a promising avenue for future research. Assessing the role of anesthetics in immunomodulation in the surgical setting is challenging, and results are often contradictory. Indeed, there is a scarcity of data of studies on humans, which hinder the interpretation of results. However, promising evidence has been published that cancer progression can be delayed by the administration of specific anesthetic agents.
Keywords: oncology